Gigi & Nate [videorecording (DVD)] - Hudgins, David; Leonard-Morgan, Paul; Bloom, Annie; Davis, Elliot, 1948-; Harden, Marcia Gay; Rowe, Charlie; Langford, Josephine, 1997-; Colletti, Zoe Margaret; Riley, Hannah; Compère, Sasha; Prada, Mishel; Belushi, James, 1954-; et al. (Roadside Attractions, 2022)
Nate suffers a near-fatal illness and is left a quadriplegic just weeks before departing for college. As Nate tries to adjust to his new life challenges, his mother helps him bring home an unlikely service animal, Gigi, a curious and intelligent capuchin monkey. Nate and Gigi form an unbreakable bond, but when it's threatened by a group trying to outlaw capuchins, Nate's family rallies behind him to help him regain the hope he so desperately needs.